Externality Effects of Sachet and Plastic Bottled Water Consumption on the Environment: Evidence from Benin City and Okada in Nigeria (International Journal of Sustainable Development & World Policy, 2020)
This paper examines the public perception of the externality effects of sachet and plastic bottled water consumption in Benin City and Okada. The methodology applied to source for data involved both the qualitative and quantitative analysis, through the use of questionnaires with well-structured questions and informal personal interviews. 320 respondents were then selected from the four local government areas of Oredo, Egor, Ikpoba-Okha and Ovia North East that make up Benin City and Okada. The results of the study as indicated by majority of the various respondents revealed the absence of tap water supply. The wastes from sachet and plastic bottles constitute danger to our environment by blocking the water ways and hindering the draining system, depositing debris in the affected rivers, thereby creating negative externalities to our environment. The study also showed that the perennial flooding in Benin City and Okada could be associated with indiscriminate disposal of empty sachets and plastic bottles. The study recommends the following; local government authorities should try to provide waste bins in every street and these should be managed and monitored by their authorized agents. Private firms that are involved in sachet and plastic bottled water production should be encouraged to establish recycling plants that can recycle plastic wastes into other useful materials in line with renewable energy mandate. Government should properly enforce the laws against indiscriminate disposal of wastes, where offenders are punished in order to maintain proper disposal of wastes in Benin City and the entire states of the Federation.